Self-reported mental health in teenagers who received CI before the age of 2.5 years in relation to typical hearing peers and parents of both groups - Anna Persson; Ulrika Löfkvist (PLoS ONE, 2026)
Objective The aim of this study was to investigate and compare how teenagers who received cochlear implants (CI) before 2.5 years of age perceive their own mental health, in relation to peers of the same age with typical hearing (TH). Comparisons were also made between teenagers’ self-reports and their parents’ assessments in both groups. Additionally, the study explored how various background factors might be associated with mental health outcomes. Materials and methods The Strengths and Difficulties Questionnaire (SDQ), both the self-report and parent-report version, was used to assess the mental health of teenagers with CI (n = 26) and teenagers with TH (n = 57). SDQ total and subscale scores were compared between groups, between teenagers and their parents, and in relation to background characteristics collected via a questionnaire developed specifically for this study. Results No significant differences in scores were found between teenagers with CI and TH. However, among those who reported clear difficulties, the challenges had persisted for a longer period of time for the CI group. Parents of the teenagers with CI scored similarly to their children on all scales except for Peer and Emotional problems. In contrast, parents of teenagers with TH scored significantly different from their children across all scales. Conclusion The mental health outcomes by the SDQ suggest positive development trends in teenagers with CIs, when compared to findings from previous studies. These results indicate that early cochlear implantation, combined with family-centered habilitation, may establish essential conditions for improved quality of life and psychosocial well-being in this population.